2022
DOI: 10.1021/acschembio.2c00153
|View full text |Cite
|
Sign up to set email alerts
|

Active Uptake and Trafficking of Nucleoside Triphosphates In Vivo

Abstract: Modified nucleoside triphosphates (NTPs) are powerful probes and medicines, but their anionic character impedes membrane permeability. As such, invasive delivery techniques, transport carriers, or prodrug strategies are required for their in vivo use. Here, we present a fluorescent 2′-deoxyribonucleoside triphosphate “TAMRA-dATP” that exhibits surprisingly high bioavailability in vivo. TAMRA-dATP spontaneously forms nanoparticles in Mg+2-containing buffers that are taken into the vesicles of living cells and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
12
0
2
Order By: Relevance
“…In the literature, native triphosphate nucleosides exhibit poor cell permeability [24] . Recently, Hocek et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, native triphosphate nucleosides exhibit poor cell permeability [24] . Recently, Hocek et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, native triphosphate nucleosides exhibit poor cell permeability. [24] Recently, Hocek et al have reported the transfection of modified dNTP using a unique transporter, synthetic nucleoside triphosphate transporter (SNTT). [25] However, nucleosides and related molecules are prodrugs for various diseases including antiviral, anticancer, and antibiotic drugs.…”
Section: Chembiochemmentioning
confidence: 99%
“…In addition to phenotypic classifications possible from fluorescently tagged proteins or anatomical regions such as the gut, body wall, pharynx or neurons, the three-fluorescent channel capability of LSC would, in principle, enable colocalization and multiplexed assay formats ( Auld et al, 2006 ). For example, metabolic incorporation of TAMRA-dATP into genomic DNA or ‘cell painting’ could facilitate a range of phenotypic profiles in C. elegans ( Gustafsdottir et al, 2013 ; Schreier et al, 2022 ). Although we conducted the current study with LSC, using automated microscopy as a primary or LSC-coupled output is certainly feasible ( Gosai et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to phenotypic classifications possible from fluorescently tagged proteins or anatomical regions such as the gut, body wall, phalanx, or neurons, the three fluorescent channel capability of LSC would in principle enable colocalization and multiplexed assay formats (Auld et al, 2006). For example, metabolic incorporation of TAMRA-dATP into genomic DNA or “cell painting” could facilitate a range of phenotypic profiles in C. elegans (Gustafsdottir et al, 2013; Schreier et al, 2022). While we conducted the current study with LSC, using automated microscopy as a primary or LSI-coupled output is certainly feasible (Gosai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%